Productivity and income of rubber farmers in Belitang II District, East Ogan Komering Ulu Regency, South Sumatra Province - Ari, Dewa Ayu Putu Setia; Sri Budhi, Made Kembar (Jurnal Ekonomi Kuantitatif Terapan, 2023)
The productivity of rubber in Belitang II Sub-district has decreased quite deeply from 2016 – 2020. The decline in the productivity of rubber farmers will affect the income earned by farmers. Belitang II sub-district is a sub-district that has a larger area of ??land and rubber production compared to other sub-districts in Ogan Komering Ulu Timur Regency, South Sumatra Province. This research is an associative quantitative research. The method of determining the sample using simple random sampling with a sample size of 97 respondents. The data analysis technique used descriptive statistical analysis and inferential statistical analysis, namely path analysis. The results of the study show that 1) land ownership, education level, and work culture have a positive effect on productivity, 2) land ownership area, education level, work culture, and productivity have a positive effect on income, and 3) land ownership area, indirectly does not directly affect income through productivity, while the level of education, and work culture indirectly affect income through productivity. Local governments are expected to strive to produce agricultural innovations to support land productivity and become a driving force in the agricultural sector, especially rubber. Keywords: Land ownership, education level, work culture,                      productivity, income